Differential Erosion and Sedimentation Process at the Longmenshan Foreland Basin, Eastern Margin of the Tibetan Plateau: Evidence From Analog Experiments - Luo, Qiang; Deng, Bin; Guang, Youhui; He, Yu; Guo, Hongbin; Huang, Jiaqiang; Yang, Rongjun; Yu, Hao; Zhang, Jing (Frontiers in Earth Science, 2021)
We use analog experiments to investigate the influence of rapid ﬁlling of foreland basin system during the development of fold-and-thrust belt, in particular, the change of erosion–sedimentation along the strike in the Longmenshan foreland basin. A negative relationship between wedge geometries (i.e., length and height) and the magnitude of erosion can be found; increased erosion results in out-of-sequence thrusting and fault reactivation in the wedge hinterland, to limit the forelandward propagation of the wedge. In contrast, increased sedimentation facilitates the forelandward propagation of the wedge. We focus on a natural example of the Longmenshan foreland basin, where a change in erosion–sedimentation along the strike during the Late Cretaceous to Cenozoic is well documented. The comparison between our model and seismic sections indicates that such a change along the strike result in a rejuvenated foreland basin restricted to the southwestern part of the western Sichuan Basin in the Cenozoic.